MicroRNA functions in osteogenic differentiation of periodontal ligament stem cells: a scoping review - Limlawan, Pirawish; Vacharaksa, Anjalee (Frontiers in Oral Health, 2025)
This scoping review aimed to describe the differential microRNA (miRNA) functions in osteogenic differentiation of periodontal ligament stem cells (PDLSCs), and then analyze the potential of applying PDLSCs and miRNAs in bone regeneration. The databases of PubMed, Google Scholar and EBSCO search were performed by the 4 themes, including periodontal ligament stem cells, miRNA, osteogenic differentiation, and tissue regeneration. The original articles described miRNA functions in osteogenic differentiation of PDLSCs were identified and selected for content analyze. The articles suggested that PDLSCs have high potential in bone regeneration because of their multipotency and immunomodulation. PDLSCs are conveniently accessible and obtained from extracted teeth. However, recent evidence reported that PDLSCs of various origins demonstrate differential characteristics of osteogenic differentiation. Exosomal miRNAs of PDLSCs demonstrate a regulatory role in tissue regeneration. The properties of PDLSCs associated to miRNA functions are altered in differential microenvironmental conditions such as infection, inflammation, high-glucose environment, or mechanical force. Therefore, these factors must be considered when inflamed PDLSCs are used for tissue regeneration. The results suggested inflammation-free PDLSCs harvested from the middle third of root surface provide the best osteogenic potential. Alternatively, the addition of miRNA as a bioactive molecule also increases the success of PDLSCs therapy to enhance their osteogenic differentiation. In conclusion, Exosome-derived miRNAs play a key role in PDLSCs osteogenic differentiation during tissue regeneration. While the success of PDLSCs in tissue regeneration could be uncertain by many factors, the use of miRNAs as an adjunct is beneficial for new bone regeneration.